Estudo comparativo das características organizacionais e nível de efetividade estratégica entre os segmentos da construção civil e da indústria de manufatura - Fisch, Rodrigo Gonçalves (2017)
Given the global economic context, two models of organization that deserve to be highlighted for their economic and social importance in the country are the construction industry and the manufacturing industry. However there are particularities that distinguish these two segments. While most industries go through an intense process of transformation, seeking agility and eliminating wastage, indispensable for survival, construction is still timid in this transformation. In this sense, an applied, descriptive and quantitative research was developed with the purpose of comparing the organizational and strategic characteristics between the segments of the civil construction industry and the manufacturing industry and to identify which of these characteristics present differences, or possibly affinity. The comparison between processes and characteristics is beneficial to contribute to the development and growth of companies, with the purpose of optimizing resources through professionalization and standardization of processes. The methodology used to collect the data was the survey method by application of questionnaires. Descriptive statistics techniques, nonparametric inferential analysis and discriminant analysis were used for analysis. It was observed that both segments had similar concerns for most of the characteristics, but some with different intensities that allow inferring to be a consequence of the segment of performance.